Zweiter Beitrag zur Kenntnis der geographischen Verbreitung der Tineiden auf der Iberischen Halbinsel (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There is given a second contribution to the Tineid fauna of the Iberic Peninsula. The present state of the exploration is discussed, showing the regions of Spain and Portugal, where further investigations are needed to complete our present knowledge. A check list of the Iberic Tineids enumerates 60 species known up to now, their synonymy, and their distribution. Nomenclatural Actsandalusiella Petersen, 1964 (Novotinea), spec. n.